The Effect of Return on Assets (ROA), Debt to Equity Ratio (DER), Asset Growth and Firm Size on Firm Value (Study on Telecommunications Sub-Sector Companies Listed on the Indonesia Stock Exchange Period 2020–2022) - Jacob William Marriott; Lorina Siregar Sudjiman (Analitika: Journal of Economics, Management, and Business, 2026)
This study investigates the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), Asset Growth, and Firm Size on Firm Value (Price to Book Value/PBV) in 10 telecommunications sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2022 period. A quantitative causal associative approach was applied using secondary panel data from annual financial reports, yielding 30 observations via purposive sampling. Multiple linear regression with classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) was employed using IBM SPSS Statistics version 26. Simultaneous testing confirms that all four variables significantly affect PBV (F = 18.764; sig. = 0.000; R² = 0.672). Partially, ROA (β = 0.387; sig. = 0.000), Asset Growth (β = 0.215; sig. = 0.027), and Firm Size (β = 0.078; sig. = 0.003) each exert a positive and significant effect on PBV, while DER (β = −0.124; sig. = 0.129) has no significant effect. Grounded in Signalling Theory, these findings demonstrate that profitability, expansion capacity, and firm scale transmit stronger value signals to investors than leverage in the post-pandemic digital transformation era.